Índice de floculação e agregação de um Latossolo Vermelho sob dois sistemas de colheita da cana-de-açúcar - de Almeida, Cinara Xavier [UNESP]; Centurion, José Frederico [UNESP]; Jorge, Ricardo Falqueto [UNESP]; Andrioli, Itamar [UNESP]; Vidal, Anelisa de Aquino [UNESP]; Serafim, Renata Soares [UNESP] (My University, 2009)
The objective of this work was to evaluate the soil physics and chemical attributes of Rhodic Ferralsol, in sugarcane systems harvest compared with soil forest. The treatments were consisted by native forest, manual and mechanized sugarcane harvesting. The soil was sampled at 0-0.10; 0.10-0.20 and 0.20-0.30 m soil depths. The soil organic matter, pH and PCZ values, flocculation degree and soil aggregation were evaluated in each soil sample. The statistics analysis was carried in a split-plot completely randomized design with five replications, exception for the soil aggregation, with six replications The soil under MN, the soil organic matter and aggregates percentage (7.93 mm class) were higher. The higher mean weigh diameter aggregates was observed at 0-0.20 soil depth, in MN.
Flocculation degree and aggregation in a Rhodic Ferralsol under sugarcane harvest systems
Keywords: Manual sugarcane harvesting; Mechanized sugarcane harvesting; Saccharum sp.; Soil organic matter; Soil quality